2021
DOI: 10.3390/s21020617
|View full text |Cite
|
Sign up to set email alerts
|

CAFD: Context-Aware Fault Diagnostic Scheme towards Sensor Faults Utilizing Machine Learning

Abstract: Sensors’ existence as a key component of Cyber-Physical Systems makes it susceptible to failures due to complex environments, low-quality production, and aging. When defective, sensors either stop communicating or convey incorrect information. These unsteady situations threaten the safety, economy, and reliability of a system. The objective of this study is to construct a lightweight machine learning-based fault detection and diagnostic system within the limited energy resources, memory, and computation of a W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…In the past, ML-based approaches have been effectively used on a variety of classification problems [52][53][54][55][56]. We used a deep learning-based scheme called ResNet in this work to identify different human activities and detect falling using the generated spectrograms.…”
Section: Residual Neural Network (Resnet) For Classificationmentioning
confidence: 99%
“…In the past, ML-based approaches have been effectively used on a variety of classification problems [52][53][54][55][56]. We used a deep learning-based scheme called ResNet in this work to identify different human activities and detect falling using the generated spectrograms.…”
Section: Residual Neural Network (Resnet) For Classificationmentioning
confidence: 99%
“…Input devices collect data from the environment. They may measure temperature [ 46 ], medical parameters [ 47 ], displacement [ 48 ], pH [ 49 ], pressure [ 50 ], humidity [ 51 ], inertia [ 52 ], etc. Output devices broadcast messages to the external world.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of advanced wireless communication systems, computational power and various sensing approaches, significant advancements in the area of indoor localization have been made. Context-aware systems [13], wearable technology [14] and contactless approaches are a few of the methods that are effectively utilized to identify human activities in an indoor setting [15]. It has been shown that it is possible to identify human activities without invading the privacy of the user by employing a device that the user is wearing to detect behaviours.…”
Section: Introductionmentioning
confidence: 99%